Metode Demonstrasi Tayamum; pada Mata Pelajaran Fiqih Ibadah Praktis - Annisa Athiyah Fitri; Mona Putri; Shoqibah Wijaya Kusuma; Asep Taufik Hidayat; Wismanto Wismanto (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This research is motivated by the researcher's concern for the continuity of the teaching and learning process in the use of the fiqh subject learning method, especially in the practical learning material, according to the researcher's observations attached. The purpose of this study is to describe the implementation of the demonstration learning method for tayammum practice in class IV-B students of Madrasah Diniyah Awaliyah 1 Pekanbaru. The method used in this study is a qualitative descriptive method, namely a method that aims to describe or explain events that occur in the field. Data collection techniques consist of observation, interviews, and documentation. Data analysis used in this study consists of data reduction, data representation, and drawing Fiqh related to the practice of Tayammum Class IV-B Madrasah Diniah Awaliyah 1 Pekanbaru can motivate students to practice Tayammum properly. The results of this study indicate that the application of the demonstration method in the subject Many students of Class IV-B Madrasah Diniah Awaliyah 1 Pekanbaru seem to still be lacking in the ability to understand the practice of Tayammum. Therefore, you need to apply a direct learning method. After enrichment, many students understand how to tayammum.